Effect of Brewing Conditions on Antioxidant Properties of Ginkgo biloba Leaves Infusion - Patrycja Biernacka; Katarzyna Felisiak; Iwona Adamska; Marek Śnieg; Cezary Podsiadło (MDPI AG, 2023)
Due to the growing awareness of the importance of healthy eating in society, there is an increasing interest in the use of herbs and low-processed, natural products. Ginkgo biloba is a raw material with a high pro-health potential, which is related to the high content of antioxidant compounds. The aim of the study was to determine the relationship between the antioxidant activity of Ginkgo biloba leaf infusions and the weighted amount of leaves and brewing time. In addition, a sensory analysis of the infusions obtained was carried out. The innovation is to determine the migration of micro- and macroelements to the infusion prepared from Ginkgo biloba depending on the leaves' weight used and the brewing time. The research showed the dependence of the antioxidant activity of the infusions and the migration of microelements on the size of the dried material and the brewing time. In the publication, the main factors influencing the quality of infusions were analysed, their mutual correlations were determined, and combinations showing the highest antioxidant activity and, at the same time, the highest sensory acceptability were selected.